2004
DOI: 10.1081/jdi-120038490
|View full text |Cite
|
Sign up to set email alerts
|

Salubrious Effect of Vitamin E Supplementation on Renal Stone Forming Risk Factors in Urogenital Tuberculosis Patients

Abstract: The incidence of renal calculi has been evaluated to be 25% in urogenital tuberculosis patients. The stone could be caused due to the host, the pathogenic organism, or possibly by the treatment. Studies were carried out to find out the efficacy of vitamin E supplementation in reducing the risk of stone formation in renal tuberculosis patients. The study constituted four groups, Group I with 30 normal volunteers, the second group comprised of 36 renal tuberculosis patients (GuTb) a day before treatment. Third g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 25 publications
(25 reference statements)
1
8
0
Order By: Relevance
“…Elevated levels of this antioxidant are associated with the prevention of membrane injury and consequently, the risk of stone formation [22]. Our observation of a favourable increase in the level of plasma a-tocopherol in the white group is in agreement with previous studies that have shown enhancement of plasma antioxidant status following vitamin E ingestion [14,22].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Elevated levels of this antioxidant are associated with the prevention of membrane injury and consequently, the risk of stone formation [22]. Our observation of a favourable increase in the level of plasma a-tocopherol in the white group is in agreement with previous studies that have shown enhancement of plasma antioxidant status following vitamin E ingestion [14,22].…”
Section: Discussionsupporting
confidence: 91%
“…However, our observation that urinary calcium and oxalate did not change after vitamin E supplementation is in contrast with other studies. A reduction in these parameters has been reported in hyperoxaluric kidney stone patients (298 IU, 90 days) [11] and in urogenital tuberculosis patients (298 IU, 60 days) [14,22] following ingestion of vitamin E. In another study on the effect of vitamins C and E on biomarkers of oxidative stress, the authors [51] demonstrated that baseline values are important when determining whether decreases per se have occurred or not. They commented that values are only likely to decrease if they are not already low.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations